Systematic Review Search Methods Template - Visintini, Sarah (Université d'Ottawa | University of Ottawa, 2023)
This is my template for writing search methods for systematic reviews. It includes prompts from the PRISMA-S checklist (for reporting literature searches in systematic reviews). It is also a work in progress! So hopefully I will continue to provide updated versions as I fine tune things. (2023-03-22)
Keywords: systematic review; reporting; search